HOSPITAL-ACQUIRED INFECTIONS AND POSTOPERATIVE COMPLICATIONS IN SURGICAL DEPARTMENTS - Abdukakharova Muattarhon Fakhritdinovna; Bryantseva Yelena Vladimirovna; Nematova Nigora Urakovna (Scholar Express Journals, 2024)
To investigate the factors and conditions that contribute to the spread of hospital-acquired infections (HAIs) in medical facilities with a surgical profile.
Keywords: hospital-acquired infections; hospital purulent-septic infections; surgical site infections